Dengue vector management using insecticide treated materials and targeted interventions on productive breeding-sites in Guatemala - Rizzo Nidia; Gramajo Rodrigo; Escobar Maria; Arana Byron; Kroeger Axel; Manrique-Saide Pablo; Petzold Max (BMC, 2012)
Abstract Background In view of the epidemiological expansion of dengue worldwide and the availability of new tools and strategies particularly for controlling the primary dengue vector Aedes aegypti, an intervention study was set up to test the efficacy, cost and feasibility of a combined approach of insecticide treated materials (ITMs) alone and in combination with appropriate targeted interventions of the most productive vector breeding-sites. Methods The study was conducted as a cluster randomized community trial using "reduction of the vector population" as the main outcome variable. The trial had two arms: 10 intervention clusters (neighborhoods) and 10 control clusters in the town of Poptun Guatemala. Activities included entomological assessments (characteristics of breeding-sites, pupal productivity, Stegomyia indices) at baseline, 6 weeks after the first intervention (coverage of window and exterior doorways made of PermaNet 2.0 netting, factory treated with deltamethrin at 55 mg/m2, and of 200 L drums with similar treated material) and 6 weeks after the second intervention (combination of treated materials and other suitable interventions targeting productive breeding-sites i.e larviciding with Temephos, elimination etc.). The second intervention took place 17 months after the first intervention. The insecticide residual activity and the insecticidal content were also studied at different intervals. Additionally, information about demographic characteristics, cost of the intervention, coverage of houses protected and satisfaction in the population with the interventions was collected. Results At baseline (during the dry season) a variety of productive container types for Aedes pupae were identified: various container types holding >20 L, 200 L drums, washbasins and buckets (producing 83.7% of all pupae). After covering 100% of windows and exterior doorways and a small number of drums (where the commercial cover could be fixed) in 970 study households, tropical rains occurred in the area and lead to an increase of the vector population, more pronounced (but statistically not significant) in the control arm than in the intervention arm. In the second intervention (17 months later and six weeks after implementing the second intervention) the combined approach of ITMs and a combination of appropriate interventions against productive containers (Temephos in >200 L water drums, elimination of small discarded tins and bottles) lead to significant differences on reductions of the total number of pupae (P = 0.04) and the House index (P = 0.01) between intervention and control clusters, and to borderline differences on reductions of the Pupae per Person and Breteau indices (P = 0.05). The insecticide residual activity on treated curtains was high until month 18 but the chemical concentration showed a high variability. The cost per house protected with treated curtains and drum covers and targeting productive breeding-sites of the dengue vector was $ 5.31 USD. The acceptance of the measure was generally high, particularly in families who had experienced dengue. Conclusion Even under difficult environmental conditions (open houses, tropical rainfall, challenging container types mainly in the peridomestic environment) the combination of insecticide treated curtains and to a less extent drum covers and interventions targeting the productive container types can reduce the dengue vector population significantly.